2015
DOI: 10.1038/srep12616
|View full text |Cite
|
Sign up to set email alerts
|

Protection against dengue disease by synthetic nucleic acid antibody prophylaxis/immunotherapy

Abstract: Dengue virus (DENV) is the most important mosquito-borne viral infection in humans. In recent years, the number of cases and outbreaks has dramatically increased worldwide. While vaccines are being developed, none are currently available that provide balanced protection against all DENV serotypes. Advances in human antibody isolation have uncovered DENV neutralizing antibodies (nAbs) that are capable of preventing infection from multiple serotypes. Yet delivering monoclonal antibodies using conventional method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 33 publications
(42 reference statements)
2
86
1
Order By: Relevance
“…We believe our in-depth studies have moved pDNA/EP beyond preliminary reports, placing this platform technology on a solid foundation for clinical development. For our efficacy experiments in mice, we used doses of pDNA (5–10 μg) that are scalable for humans, in contrast to previous studies (25–300 μg) 11, 12, 13, 14, 15, 16, 17. Despite lower inoculum of pDNA, we observed higher mAb expression with mean peak serum concentrations (3–5 μg/mL) (Figure 2) that are 3- to 10-fold higher than previous findings 13, 14, 15, 16, 17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe our in-depth studies have moved pDNA/EP beyond preliminary reports, placing this platform technology on a solid foundation for clinical development. For our efficacy experiments in mice, we used doses of pDNA (5–10 μg) that are scalable for humans, in contrast to previous studies (25–300 μg) 11, 12, 13, 14, 15, 16, 17. Despite lower inoculum of pDNA, we observed higher mAb expression with mean peak serum concentrations (3–5 μg/mL) (Figure 2) that are 3- to 10-fold higher than previous findings 13, 14, 15, 16, 17.…”
Section: Discussionmentioning
confidence: 99%
“…For our efficacy experiments in mice, we used doses of pDNA (5–10 μg) that are scalable for humans, in contrast to previous studies (25–300 μg) 11, 12, 13, 14, 15, 16, 17. Despite lower inoculum of pDNA, we observed higher mAb expression with mean peak serum concentrations (3–5 μg/mL) (Figure 2) that are 3- to 10-fold higher than previous findings 13, 14, 15, 16, 17. Furthermore, mAb concentrations remained ∼1 μg/mL for up to 32 weeks (Figure 2), which is more persistent that previously described,14, 16, 17 therefore potentially extending the therapeutic window for treatment and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…26, 27, 28 Recent studies reported that this advanced plasmid DNA delivery technology was used to generate human Fab or immunoglobulin G1 (IgG1) broadly neutralizing antibody against the HIV or Dengue virus, respectively, in mouse sera after a single intramuscular injection and in vivo EP. 29, 30 To date, however, the synthetic DNA-encoded antibody approach, or DNA-based monoclonal antibody (dMAb) technique, has not been applied to tumor gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the EP vaccine approach does offer the promise of improving responses to DNA vaccination. Recently, a DNA plasmid vaccine against Dengue virus, in conjunction with EP treatment, was shown to confer protection against dengue disease in mice [80]. DNA vaccination with subsequent EP treatment has also been shown to be effective in animal models against chikungunya virus, choriomeningitis, and influenza A [8184].…”
Section: Hcmv Vaccine Technologiesmentioning
confidence: 99%